2007
DOI: 10.2304/ciec.2007.8.3.244
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Silences in Australian Early Childhood Social Policy

Abstract: Growing international interest in the early childhood years has been accompanied by an expansion of public programs in Australia targeting young children and their families. This article explores some of the influences and rhetoric that frame these initiatives. It encourages critical examination of the discourses that shape the nature of early childhood programs in Australia and identifies a range of barriers that inhibit the involvement of early childhood teachers in the design and delivery of social policy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…Thus, research investigating quality ECEC may not be seen to be about education or, alternatively, researchers may target positivist approaches and psychology journals as a strategy to highlight the importance of, and thus lift the status of, quality ECEC. Third, the positioning of quality ECEC with developmental psychology may be indicative of health and welfare agendas being privileged in government policy, and ECEC research, as well as policy, being marked by 'pedagogical silences' (Cheeseman, 2007).…”
Section: Quality Is the Domain Of Science/psychologymentioning
confidence: 99%
“…Thus, research investigating quality ECEC may not be seen to be about education or, alternatively, researchers may target positivist approaches and psychology journals as a strategy to highlight the importance of, and thus lift the status of, quality ECEC. Third, the positioning of quality ECEC with developmental psychology may be indicative of health and welfare agendas being privileged in government policy, and ECEC research, as well as policy, being marked by 'pedagogical silences' (Cheeseman, 2007).…”
Section: Quality Is the Domain Of Science/psychologymentioning
confidence: 99%
“…There needs to be a mediation of interpretations and an aligning of responses (Edwards, 2011). There is a very real risk that the important knowledge base that underpins work in the ECEC sector could well be marginalized in favour of other highly medicalised approaches such as those in medicine and associated therapies (Cheeseman, 2007). Macfarlane et al (2010) argue that this possible marginalisation of the knowledge base will become increasingly problematic, as it will limit the possibility of early years teachers and other early years educators being identified as leaders in such contexts.…”
Section: Discussionmentioning
confidence: 99%
“…However, in reality, silos of practice exist (Press & Woodrow, 2005), which act to restrict the opportunities for knowledge exchange meaning that new ideas and approaches in particular sectors are often misunderstood in others. This situation increases protectiveness of individual knowledge bases and fosters suspicion about whether decisions about particular practice approaches are evidencebased (Cheeseman, 2007). For early childhood teachers, who have long made claim to the early years' knowledge base, this current policy climate is creating significant tension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a risk, however, that when early childhood education and care programs are constructed primarily as adjuncts to programs for parents, the experiences of children and the quality of their programs can fall out of the line of vision. This blind spot might result from the assumption that children automatically benefit from support given to parents (Warin, 2006) or because the pedagogical experiences of children are not given the same priority (Cheeseman, 2007). For instance, in our studies (Press et al, 2010;Wong et al, under review), members of the research team observed instances where playgroups were established as a means of bringing parents together, but were not sufficiently organised or resourced to meaningfully engage children or to enable children to develop strong, supportive relationships with peers and caring adults outside the family.…”
Section: Framing Education and Carementioning
confidence: 99%